Uji Aktivitas Hipoglikemik Ekstrak Etanolik Daun Lenglengan ( Leucas lavandufolia,smith) pada Tikus Putih Jantan yang Dibebani Glukosa - susilowati, sri (Media Farmasi Indonesia, 2013)
ABSTRACT Empirical experience-based, Lenglengan (Leucas lavandulifolia Smith) leaves have a special antidiabetic effect. This research aimed to determine the hypoglycemic effect of ethanolic extract of Lenglengan leaves in glucose induced rats. The research was conducted by dividing the experiment animals into five groups, each group had 6 rats. Three groups were given with ethanolic extract of Lenglengan leaves with 63, 126, and 252 mg/kgBB doses. One group served as the positive control were given Metformin at 189 mg/kgBB dose and the negative control were given CMC-Na 0,5%. Thirty minutes after the experiment, the animals were given D-glukosa monohydrate peroral with 2 g/kgBB dose. The measurement of the blood glucose was conducted by taking the blood at 0, 30, 60, 120, 180, 240 and 300 minutes. The blood glucose rate was measured enzymatically using GOD-PAP reagent. The evaluation on the hypoglicemic effect was done to AUC0-300 relationship curve value between blood glucose to sampling time 0-300 minute and hypoglycemic activity percentages. The statistical analysis to data AUC was done with Kruskal-Wallis test, continued with Mann-Whitney test. The result showed that the ethanolyc extract of Lenglengan leaves at 63, 126, and 252 mg/kgBB doses could decrease the blood glucose on rats glucose induced and was proven statistically to indicate high significance in comparison to the negative control (p < 0,05). The hypoglycemic activity percentage from the ethanolic extract of lenglengan leaves at 252 mg/kgBB dose was of 45,89%, where as metformin 189 mg/kgBB doses it was of 44,86%. Keywords: extract, lenglengan, hypoglichemic effect.